ANALYSIS OF THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT (K3) AND RISK ASSESSMENT ON THE TIME PERFORMANCE OF TOLL ROAD INFRASRUCTURE PROJECTS WITH JOB SATISFACTION AS AN INTERVENING VARIABLE BASED ON SEM-PLS - Arief Satria Maulana; Budi Susetyo; Mawardi Amin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Time performance is one of the key indicators of project success, especially in toll road infrastructure projects with strict deadlines. This study aims to analyze the influence of Occupational Health and Safety (OHS) Management and Risk Assessment on Time Performance through Job Satisfaction as an intervening variable using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data were collected from workers involved in toll road infrastructure projects and analyzed using a quantitative approach.The results indicate that Risk Assessment and OHS Management have a positive and significant effect on Job Satisfaction, with path coefficient values of 15.312 and 9.116, respectively. Additionally, Job Satisfaction significantly affects Time Performance (path coefficient = 2.625). Further analysis reveals that Risk Assessment and OHS Management also have a significant impact on Time Performance through Job Satisfaction, with path coefficient values of 2.923 and 2.507, respectively. This finding suggests that effective OHS management and risk assessment processes can enhance worker satisfaction, ultimately leading to improved project completion efficiency.This study highlights the importance of integrating safety management and risk assessment into project management strategies to enhance time efficiency in toll road infrastructure projects.